1975
DOI: 10.1073/pnas.72.9.3565
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weights of adrenocorticotropic hormone in extracts of anterior and intermediate-posterior lobes of mouse pituitary.

Abstract: The molecular weight of the adrenocorticotropic hormone (ACTH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…as suggested by the com pletely different changes noted in the concentration of bio active ACTH. Corticotropic activity of PI from adult mice and rats [8,16,37] is due to peptides of high, medium and low molecular weights; various entities containing the NH:-terminal portion of 1-39 ACTH have also been demonstrat ed in rat NIL by using R1A [8,13,17,21,24]; the relative proportion of the peptides varying according to the authors. Both high (30k) and medium (20k) molecular weight pep tides have been shown to serve as precursors in the process of biosynthesis of a-MSH and other peptides [5,18]; there is a controversy with regard to occurrence and concentration of low molecular weight ACTH [13].…”
Section: Discussionmentioning
confidence: 99%
“…as suggested by the com pletely different changes noted in the concentration of bio active ACTH. Corticotropic activity of PI from adult mice and rats [8,16,37] is due to peptides of high, medium and low molecular weights; various entities containing the NH:-terminal portion of 1-39 ACTH have also been demonstrat ed in rat NIL by using R1A [8,13,17,21,24]; the relative proportion of the peptides varying according to the authors. Both high (30k) and medium (20k) molecular weight pep tides have been shown to serve as precursors in the process of biosynthesis of a-MSH and other peptides [5,18]; there is a controversy with regard to occurrence and concentration of low molecular weight ACTH [13].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of high molecular weight forms of ACTH in a variety of animal pituitaries has suggested that this peptide is also synthesized from larger precursors [4][5][6]. Several lines of evidence suggest that sequential proteolytic processing is involved in the generation of bio logically active peptides, including ACTH, a-melanocyte-stimulating hor mone (a-MSH), P-lipotropin (p-LPH), P-MSH and endorphins from a com mon precursor [7][8][9], Our study was initially conducted to elucidate the possibility that bio logically inert ACTH precursors might become biologically active when degraded into smaller fragments. When a partially purified fraction of high molecular weight ACTH.…”
Section: Introductionmentioning
confidence: 99%
“…The function of the pars intermedia of the mammalian adenohypophysis is poorly understood as yet, though it is known that this tissue synthesizes and contains a series of hormonally active substances derived from a common precursor [Mains and Eipper, 1975;Eipper and Mains, 1978;Seidah et al, 1978;Zimmerman and Kraicer, 1978;Gianoulakis et al, 1979;Nakanishi et al, 1979;Mains and Eipper, 1979]. In contrast to other endocrine tissues, the pars inter media in many mammals has a poor to virtuallv non-existent vascular supply {Howe and Maxwell, 1968;Howe, 1973;Murakami, 1975].…”
Section: Introductionmentioning
confidence: 99%